Two new species of the genus Pseudopoda Jäger, 2000 and first description of the male of Pseudopoda physematosa (Araneae, Sparassidae) from Yunnan Province, China - Yang, Zi-Zhong; Wu, Ya-Ying; Li, Zhi-Min; Zhang, Bao-Shi (Zootaxa, 2022)
Two new species of the genus Pseudopoda Jäger, 2000 are reported from Yunnan Province, China: Pseudopoda mingshengi sp. nov. (male, female) and P. uncata sp. nov. (male, female). The male of P. physematosa Zhang, Jäger & Liu, 2019 is described for the first time.